Fraud Diamond Dalam Mendeteksi Financial Statement Fraud Pada Perusahaan Manufaktur - Susanto Salim, Ivan Andrean, (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2021)
The purpose of this study is to analyze the detection financial statement fraud using fraud diamond perspective. The variable in this study consists of financial statement fraud as dependent variable and fraud diamond such as financial target, financial stability, monitoring effectiveness, nature of industry, auditor change, and director change as the independent variables. This study used purposive sampling on manufacturing company listed in the Indonesia Stock Exchange from 2018-2020 period with a total observation of 166 sample. Multiple linear regression is used to analyze the use of fraud diamond on detecting financial statement fraud. The research finds that nature of industry, and financial stability have significant effect on financial statement fraud. Contrarily, variables such as financial target, monitoring effectiveness, auditor change, and director change have no significant effect on financial statement fraud. Thus, only nature of industry, and financial stability can be used to detect financial statement fraud.Â